The Celebes Molasse: A revised Neogene stratigraphy for Sulawesi, Indonesia. (1st May 2022) - Nugraha, Abang Mansyursyah Surya; Hall, Robert; BouDagher-Fadel, Marcelle
Graphical abstract: Highlights: Review of Neogene stratigraphy of Sulawesi based on new field and laboratory work. Celebes Molasse includes sediments of different age and depositional environment. Early Miocene unconformity marks collision of the Sula Spur microcontinent. Younger unconformities not related to collisions but due to extension. Extension mainly resulted from subduction rollback. Abstract: Over the past century, a wide variety of poorly dated sediments that unconformably overlie pre-Neogene rocks in Sulawesi have been assigned to the Celebes Molasse and interpreted as post-orogenic rocks deposited after a major collision. New data from fieldwork and laboratory studies, including mineralogical, palaeontological and zircon geochronological analyses, provide the basis for a new Neogene stratigraphy and show that sediments assigned to the Celebes Molasse have significant variations in age, environment of deposition, composition and sedimentation history. Identified unconformities in the (1) Early Miocene (c. 23 Ma), (2) Middle Miocene (c. 15 Ma), (3) Mio-Pliocene (c. 6–5.3 Ma), and (4 and 5) Pleistocene (c. 1.8 and 0.1 Ma) separate Lower Miocene, Middle to Upper Miocene, Pliocene, Pleistocene and Holocene mega-sequences. These mega-sequences resulted from Early Miocene collision followed by extension, driven by subduction rollback, causing both uplift and subsidence, in contrast to previous interpretations of multiple collisions.